Electrochemical Sensors Based on Carbon Nanomaterial Used in Diagnosing Metabolic Disease - Zhang, Congcong; Du, Xin (Frontiers in Chemistry, 2020)
Metabolic diseases have become common diseases with the improvement of living standards because of changed dietary habits and living habits, which seriously affect health. Currently, related biomarkers have been widely used as important indicators for clinical diagnosis, treatment, and prognosis of metabolic diseases. Among all detection methods for biomarkers of metabolic diseases, electrochemical sensor technology has the advantages of simplicity, real-time analysis, and low cost. Carbon nanomaterials were preeminent materials for fabricating electrochemical sensors in order to enhance the performance. In this paper, we summarize the research progress in the past 3 years of electrochemical sensors based on carbon nanomaterials in detecting markers of metabolic diseases, which include carbon nanotubes, graphene, carbon quantum dots, fullerene, and carbon nitride. Additionally, we discuss the future prospects for this field.